Dose‐dependent effects of continuous positive airway pressure for sleep apnea on weight or metabolic function: Individual patient‐level clinical trial meta‐analysis. (19th November 2018) - Hoyos, Camilla M.; Murugan, Swati M.; Melehan, Kerri L.; Yee, Brendon J.; Phillips, Craig L.; Killick, Roo; Cayanan, Elizabeth A.; Wong, Keith K.; Liu, Peter Y.; Grunstein, Ronald R.; Marshall, Nathaniel S.
Summary: Therapeutic‐continuous positive airway pressure seems to increase weight compared with placebo‐continuous positive airway pressure. It is not known whether weight gain with therapeutic‐continuous positive airway pressure dose is dependent or whether it causes metabolic dysfunction. Data synthesis of three randomised placebo‐continuous positive airway pressure‐controlled trials (2–3 months) was performed to test whether there is a dose‐dependent effect of continuous positive airway pressure on weight. Fasting glucose, insulin, insulin resistance (homeostatic model assessment), lipids and visceral abdominal fat were also tested to determine any effect on metabolic function. Mixed‐model analysis of variance was used to quantify these effects. One‐hundred and twenty‐eight patients were analysed. Overall there was a small increase in weight with therapeutic‐continuous positive airway pressure use compared with placebo‐continuous positive airway pressure (difference: 1.17 kg; 0.37–1.97, p = 0.005), which was greater with high‐use therapeutic‐continuous positive airway pressure compared with high‐use placebo‐continuous positive airway pressure (1.45 kg; 0.10–2.80, p = 0.04). Continuous positive airway pressure use as a continuous variable was also significantly associated with weight change in continuous positive airway pressure users (0.30 kg hr −1 night −1 ; 0.04–0.56, p = 0.001), but not in placebo users (0.04 kg hr −1 night −1 ; −0.22 to 0.26, p = 0.76). Neither therapeutic‐continuous positive airway pressure nor the dose of therapeutic‐continuous positive airway pressure caused any changes to metabolic outcomes. The weight gain effects of medium‐term therapeutic‐continuous positive airway pressure appear modest and are not accompanied by any adverse metabolic effects.